Técnicas de control clásico con temperatura externa en sistemas de aire acondicionado tipo Mini-Split (2018)
The air conditioning systems (AC), are technologies developed to provide thermal comfort in a closed room. The high temperatures of the environment (external temperature) affect the operation of an AC system, generating overexertion in the system, even when it cannot reach the desired temperature value (set-point). This overexertion causes the system to consume more energy without achieving its objective. In the current state of the literature it is evident that the external temperature is a little used factor to improve the efficiency in AC systems. Therefore, the present work realizes the implementation of two classic control techniques: Linear and PI, which include the external temperature as variable of the control loop. The control system that is designed here is applied to a mini-split type AC system, to verify the energy consumption when applying these control techniques.